FACTORS AFFECTING WITH THE PREVALENCE OF HYPERTENSION IN PREGNANCY: SCOPING REVIEW - Yuriah, Siti; Kartini, Farida (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Hypertension is a clinical term to describe the pressure of high blood which cause fetal morbidity due to reduced blood flow to the placenta, such as stunted fetal growth, fetal death in utero to premature birth to cause maternal morbidity such as pulmonary edema, bleeding in the brain, eclamptic seizures, blood clots in the veins, acute kidney failure and even death in the mother. Hypertension in Pregnancy is a major complication that causes 60% to 80% of maternal deaths and maternal morbidity in the worldwide. The purpose of this scoping review is to determine the factors that influence the incidence of hypertension in pregnancy.Method: Scoping Review uses the following databases: Pubmed, Wiley Online Library, and ProQuest. Search results that meet the criteria will then be parsed into articles. Study Use of the Joana Briggs Institute/JBI and synthetic methods using transforming PEOS.Results: From the 108 articles related to the title and abstract, 9 articles met the inclusion and exclusion criteria. Five factors were found, namely heredity, age, parity, gemeli and Body Mass Index/ BMI that affected Hypertension in Pregnancy. Conclusion: Hypertension in pregnancy was 5-15% and it was a significant complication in pregnancy. Due to the etiology was still not clearly detected and the referral system was not definitely still perfect. It also indicated that five factors could affect the occurrence of hypertension in pregnancy which are, heredity, age, multiple pregnancies, parity, and body mass index.